Using Monte Carlo Simulation to Calculate The Dose Reduction at The Maze Entrance of A Radiotherapy Room - Bari, Dindar Sh. (Science Journal of University of Zakho, 2014)
The aim of this study was to introduce a method to reduce the dose of the backscattered photons from a linear accelerator at the maze entrance of a radiotherapy room (RR). For this purpose a typical RR was designed and simulated using FLUKA Monte Carlo Code (version 2011.2b.1). The maze of a RR was the main focus for the study. Its walls including, floor and ceiling were lined with thin sheets of lead and stainless steel of 2 mm and 4 mm thicknesses respectively to find the most effective material and thickness for dose reducing. It was found that 2 mm lead sheet was able to reduce the dose at the maze entrance by more than 60 % and 4 mm 70 %. Whereas, 2 mm of stainless steel was able to reduce about 30% of the dose and 4 mm was able to reduce about 35%.